Una mirada al emprendimiento social en Colombia - Mongui Pinentel, Javier; López Fernández, José Pastor; Yepes González, Edwin Gregorio; Baquero, Edward Leonardo; Parra Barrios, Hernando (Corporación Universitaria Minuto de Dios - UNIMINUTO, 2023)
Este libro producto de investigación, integra una revisión de literatura, examina el emprendimiento social en Colombia, su contexto, gestión financiera, formación y estrategias que ayudan a comprender su desarrollo, identificar los recursos, evaluar riesgos y comenzar con éxito un emprendimiento.

A look at social entrepreneurship in Colombia is a book result of a research based on a literature review, since it provides knowledge in three chapters, starting with the international and national context, contemplating the main characteristics for the operation of entrepreneurship and presenting alternatives for financial management as a tool for proper decision making, thus seeking to provide support for teaching, research and social projection. Next, it is oriented to the training of social entrepreneurs, by addressing current topics described from project planning to the creation of impact strategies. The content helps readers to understand how to develop an entrepreneurial culture in Colombia, to identify resources and to start successfully assessing the risks associated with entrepreneurship.
Keywords: Emprendimiento; Emprendimiento social; Colombia; Gestión financiera; Formación y estrategias; 658.408; Social entrepreneurship; Financial management; Operation; Responsabilidad social en los negocios - Estudio de casos; Gestión financiera - Colombia; Administración de proyectos - Colombia; Empresas - Aspectos sociales; Liderazgo - Colombia; Emprendimiento social